2019
DOI: 10.33023/jikep.v5i2.237
|View full text |Cite
|
Sign up to set email alerts
|

Pengetahuan Mahasiswa Keperawatan Tentang Sasaran Keselamatan Pasien

Abstract: The people’s demands for service satisfaction and patient safety during care were a major challenge for the world of nursing. Students must be equipped with adequate knowledge, attitudes and skills in implementing the patient safety goals program. The purpose of this study was evaluate the knowledge and learning experience of students towards Patient Safety Goals (PSG). Descriptive research was conducted on 71 level II students who had obtained patient safety subject chosen by convenient sampling technique. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…However, a nurse in carrying out nursing actions not only promotes selfconfidence, but also knowledge, skills, attitudes and morals in providing services to clients. Study conducted on nursing students found that knowledge and skills Nurses are very important so that they affect client safety (Nuryanti, 2019). Besides that, other studies also state that attitudes and morals are no less important aspects effect on client safety in health services (Lim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, a nurse in carrying out nursing actions not only promotes selfconfidence, but also knowledge, skills, attitudes and morals in providing services to clients. Study conducted on nursing students found that knowledge and skills Nurses are very important so that they affect client safety (Nuryanti, 2019). Besides that, other studies also state that attitudes and morals are no less important aspects effect on client safety in health services (Lim et al, 2017).…”
Section: Discussionmentioning
confidence: 99%